Great Christian Thinkers - Küng, Hans (London SCM Press, 1994)
Overview: Kung assesses the teachings and writings of the men whom he deems to be the greatest Christian thinkers of the past two millennia, discussing the significance of each thinker's work and life, and showing how he affected the trajectory of Chris
Keywords: Paul, -- the Apostle, Saint -- Studies. Origen -- studies. Augustine, -- Saint, Bishop of Hippo -- Studies